Implicações da desfolha precoce e da proteção química à mancha branca na cultura do milho - Rezende, Wender Santos (2014)
Maize is one of the main crops in Brazil and the world, and its production is highly demanded for human and animal consumption. Maintenance of leaf integrity is required by the crop to reach high yield. Therefore, this study evaluated the effect of defoliation at the beginning of the crop cycle and the combination of fungicides to control white spot disease in maize. This study was divided into two trials. The first one evaluated the effect of defoliation in vegetative stage V4 on maize development and yield. Six experiments were conducted in different years and locations, representing different environments, besides different investment levels. The experimental design was randomized complete block with four defoliation levels (treatments), and seven replicates. Defoliation was performed manually in maize vegetative stage V4, with treatments consisting of removal of the two basal leaves, removal of four fully expanded leaves, plant section (removal of all leaves), besides a control. Duration of vegetation period and, previously to harvest, plant height, main ear insertion height, breaking strength of stalk, force required to pull the plant and kernel productivity were evaluated. It can be concluded that removal of four leaves and the section of the plant in V4 stage hinders plant growth, delays flowering and greatly reduces yield. The second study evaluated combination of fungicides to control maize white spot and maize response to chemical protection in field conditions. Four experiments were done in different years and locations. The experimental design was randomized blocks with seven treatments and six replications. The treatments were: dithiocarbamate with two or three applications, strobilurin + triazole with two or three applications, strobilurin + triazole + dithiocarbamate with two or three applications and a control treatment (without fungicide). White spot severity of maize was evaluated for the calculation of AUDPC, percentage of green leaf area at the end of the crop cycle, stem integrity (stalk density, stalk breaking strength, breaking height and angle), percentage of rotten kernels and kernel yield. It can be concluded that the combination of dithiocarbamate and the pre-mix of strobilurin and triazole, with two or three applications, was effective to control the maize white spot. The use of three applications of dithiocarbamate is also effective in controlling this disease. The effective treatments to control maize white spot also provided greater green leaf area, greater stalk integrity and yield. The maintenance of leaf area is important throughout the crop cycle for the expression of its yield potential, and the use of fungicides contributes for this maintenance.